Work–family conflict, psychological availability, and child emotion regulation: Spillover and crossover in dual‐earner families. Issue 3 (11th July 2017) - MATIAS, MARISA; FERREIRA, TIAGO; VIEIRA, JOANA; CADIMA, JOANA; LEAL, TERESA; M. MATOS, PAULA
Abstract: Work–family balance and child rearing are major social concerns. Few studies, however, have addressed how parents' work–family conflict (WFC) associates with children's emotion regulation. This study proposes the link to occur through parents' psychological availability (PA). In our model we tested both intraindividual and interindividual effects on a sample of 138 dual‐earner couples with preschool‐aged children. Our results showed that WFC related negatively to PA (actor and partner effects); fathers' and mothers' PA associated negatively with child lability and positively with child emotion regulation. Indirect effects were found for fathers' and mothers' WFC and children's emotion regulation and lability through partners' PA, controlling for child gender and temperament. These findings showed a dyadic pattern among couples' work–family balance, parenting, and children's emotion regulation.